2016
DOI: 10.1111/jpi.12344
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin attenuates neuronal apoptosis through up‐regulation of K+Cl cotransporter KCC2 expression following traumatic brain injury in rats

Abstract: Traumatic brain injury (TBI) initiates a complex cascade of neurochemical and signaling changes that leads to neuronal apoptosis, which contributes to poor outcomes for patients with TBI. The neuron-specific K(+) -Cl(-) cotransporter-2 (KCC2), the principal Cl(-) extruder in adult neurons, plays an important role in Cl(-) homeostasis and neuronal function. This present study was designed to investigate the expression pattern of KCC2 following TBI and to evaluate whether or not melatonin is able to prevent neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 50 publications
1
53
0
Order By: Relevance
“…Accordingly, it has been identified that BDNF/CREB pathway is suppressed in AD brain as well as at the neurons treated with Aβ . Besides, melatonin can attenuate the downregulation of BDNF and protect against neuronal apoptotic during brain damage in rats . Thus, we propose that melatonin might rescue Aβ‐induced neurotoxicity via increasing the level of BDNF and elevating the expression of miR‐132 correspondingly.…”
Section: Discussionmentioning
confidence: 86%
“…Accordingly, it has been identified that BDNF/CREB pathway is suppressed in AD brain as well as at the neurons treated with Aβ . Besides, melatonin can attenuate the downregulation of BDNF and protect against neuronal apoptotic during brain damage in rats . Thus, we propose that melatonin might rescue Aβ‐induced neurotoxicity via increasing the level of BDNF and elevating the expression of miR‐132 correspondingly.…”
Section: Discussionmentioning
confidence: 86%
“…The TBI model was established by controlled cortical impact (CCI) as described previously 16 . The CCI model was shown in Figure S1.…”
Section: Methodsmentioning
confidence: 99%
“…The pathophysiology of TBI Traumatic brain injury is characterized by instant damage to mechanical force and delayed damage to the subsequent pathophysiological processes [21]. The mechanical force directly leads to neuronal or diffuse axonal damage and vascular disruption, followed by secondary injury mediated by extensive neuroinflammation, dysfunction of the BBB, oxidative stress, and apoptosis [22][23][24][25][26]. While the immediate primary injury is considered untreatable, the delayed secondary injury gives a window for intervention and has, therefore, attracted a lot of attention [27].…”
Section: Introductionmentioning
confidence: 99%